The interplay of nutrients and tree invasion shapes the plant community in heathland habitats. Issue 1 (January 2017) - Fagúndez, Jaime
Abstract: Can drivers of temporal vegetation changes and their interactions be modelled in dynamic ecosystems? Kepfer‐Rojas et al., in this issue of Applied Vegetation Science, studied species richness and cover in an unmanaged heathland to address this topic. Complex interactions between drivers and their degree of spatial dependence condition the success of each functional group, in a scenario of permanent competition. Abstract : Can drivers of temporal vegetation changes and their interactions be modelled in dynamic ecosystems? Kepfer‐Rojas et al., in this issue of Applied Vegetation Science, studied species richness and cover in an unmanaged heathland to address this topic. Complex interactions between drivers and their degree of spatial dependence condition the success of each functional group, in a scenario of permanent competition.